"Hello group, I need advice": A Textual Analysis of Black Fathers' Help‐Seeking Posts on Facebook. Issue 5 (2nd October 2020) - McLeod PhD, MSW, Branden A.
Abstract : Objective: To explore the types of advice and help that Black fathers seek from one another on a Facebook group dedicated to fathers. Background: Research demonstrates that Black men are less likely to seek help from formal supports when dealing with life stressors. Informal supports, such as social networks, can help facilitate access to formal support services. Parents use social media for social support; yet a dearth of research exists that explores how Black fathers use social media for social support. Methods: A keyword search for "advice" amassed 137 Facebook posts generated by 134 fathers. An inductive textual analysis assisted in interpreting fathers' posts to explore prominent themes. Results: Eighty percent of all posts addressed five dominant themes for advice, including family expansion, financial matters, maternal gatekeeping, navigating family relationship conflict, and raising children and child development. Conclusion: This study finds that Black fathers' express their strengths to one another and present nuanced familial challenges via social media. Implications: Formal service systems should consider supplementing existing services and encourage virtual and informal social support networks. Informal and virtual social support networks could be convened and moderated by fathers in a grassroots format.